Rethinking, reducing, and refining the classical oral tyramine challenge test of monoamine oxidase (MAO) inhibitors - Ewoud‐Jan vanHoogdalem; Karen L. Smith; Jan Hartstra; John Constant (Wiley, 2023)
Abstract The oral tyramine challenge evaluates the safety of novel monoamine oxidase (MAO) inhibitors when taken with tyramine‐containing food or drinks. In its current design, it comprises an extensive series of tyramine escalation steps until a blood pressure threshold is met. Due to the high variation in tyramine bioavailability, and thereby in blood pressure effect, this classical design has various limitations, including safety concerns. Based on data from a previously performed tyramine challenge study, the present study explored a reduced new design that escalates up to 400 mg, and evaluates the dose to a tyramine peak plasma concentration of ≥10 ng/mL, instead of a dose up to 800 mg, and to a blood pressure change of ≥30 mm Hg. Tested by trial simulation, the new design proves more efficient than the classical design in terms of better identifying tyramine sensitivity of test and reference treatments and reducing false‐positive and false‐negative rates in estimating tyramine sensitivity by more than 10‐fold. Since it escalates over a lower tyramine dose range, the new design reduces risk to subjects associated with tyramine‐induced blood pressure excursions, is less demanding for study participants, and is more efficient. By its focus on tyramine bioavailability as the primary concern for novel MAO inhibitors, the new tyramine challenge study provides better answers in a simplified and safer design compared with the classical design in trial simulation, warranting its use in future clinical studies.